Molecular Mechanisms Underlying the Regulation of Biofilm Formation and Swimming Motility by FleS/FleR in Pseudomonas aeruginosa - Zhou, Tian; Huang, Jiahui; Liu, Zhiqing; Xu, Zeling; Zhang, Lian-hui (Frontiers in Microbiology, 2021)
P. aeruginosa, a major cause of nosocomial infection, can survive under diverse environmental conditions. Its great adaptive ability is dependent on its multiple signaling systems such as the two-component system (TCS). A TCS FleS/FleR has been previously identified to positively regulate a variety of virulence-related traits in P. aeruginosa PAO1 including motility and biofilm formation which are involved in the acute and chronic infections, respectively. However, the molecular mechanisms underlying these regulations are still unclear. In this study, we first analyzed the regulatory roles of each domains in FleS/FleR and characterized key residues in the FleS-HisKA, FleR-REC and FleR-AAA domains that are essential for the signaling. Next, we revealed that FleS/FleR regulates biofilm formation in a c-di-GMP and FleQ dependent manner. Lastly, we demonstrated that FleR can regulate flagellum biosynthesis independently without FleS, which explains the discrepant regulation of swimming motility by FleS and FleR.